A SURVEY ABOUT THE ATTITUDE TOWARDS COVID-19 VACCINATION AMONG THE STUDENTS AT THE FACULTY OF MEDICINE – SKOPJE, REPUBLIC OF NORTH MACEDONIA - Bogdanska, Jasna; Topuzovska, Sonja; Tosheska Trajkovska, Katerina; Cekovska, Svetlana; Ampova, Hristina; Emin, Melda; Stanojevska Petrushevska, Elena; Duma, Irma; Grujoska-Veta, Dushanka (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
The SARS-Cov-2 virus represents the most important challenge for public health worldwide. In order to prevent the spread of the virus, vaccines from different suppliers were introduced in the Republic of North Macedonia. Bearing in mind that vaccination against COVID-19 is not obligatory, the present survey was designed in order to evaluate the personal attitude towards vaccination among the first and second year students at the Medical Faculty in Skopje. In total, 427 students consented for participation in the survey. Overall, 46% out of all participants considered that vaccination should be mandatory among the healthcare workers and medical students. Most of the participants, overall 75% of total, expressed the willingness to receive the vaccine for the sake of public health and for their own families. Fifty-three percent of the students were willing to receive the vaccine from any manufacturer in order to contribute to the public health, but most of them have expressed their willingness to live with the restrictive measures for an unlimited time. The overall attitude towards general vaccination was highly positive (84% of all participants). We can conclude that, most of the first and second year students at the Medical Faculty, have expressed their willingness to receive the vaccine against Covid-19. Key words : attitude towards Covid-19 vaccine, attitude towards vaccination. https://doi.org/10.55302/JMS2143114b